Respuesta :
multiply the constants, add up the exponents
4*(-3)*(-7)=84
1+8+3=12
so the result is 84x^12
4*(-3)*(-7)=84
1+8+3=12
so the result is 84x^12
Answer:
The simplified form of given expression is [tex]84(x^{12})[/tex].
Step-by-step explanation:
The given expression is
[tex](4x)(-3x^8)(-7x^3)[/tex]
We need to find the product of given expression.
First multiply the coefficients.
[tex](4)(-3)(-7)(x)(x^8)(x^3)[/tex]
[tex]84(x)(x^8)(x^3)[/tex]
Using power property of exponent, we get
[tex]84(x^{1+8+3})[/tex] [tex][\because x^mx^n=x^{m+n}][/tex]
[tex]84(x^{12})[/tex]
Therefore the simplified form of given expression is [tex]84(x^{12})[/tex].